Corrigendum to "Einstein Riemannian metrics and Einstein–Randers metrics on a class of homogeneous manifolds" [Nonlinear Anal.: TMA 107 (2014) 86–91]. (January 2016) - Kang, Yifang; Chen, Zhiqi
Abstract: We correct Theorem 3.2 of Kang and Chen (2014), and then make corresponding changes to the description of Corollary 3.3, Theorem 3.5, and Theorem 4.3 of Kang and Chen (2014).